Financial Feasibility of Sijuk Shrimp Paste Business in Sungai Padang Village, Sijuk District, Belitung Regency - Aditya Nugraha; Suhatmini Hardyastuti; Jangkung Handoyo Mulyo (Agro Ekonomi, 2017)
Sijuk shrimp paste business is a business in processing rebon shrimp which is most commonly implemented in Belitung Regency. In this study, profi t analysis, investment feasibility, and sensitivity were used to draw the conclusions. The samples involve 25 shrimp paste businesses taken by using census method in Sungai Padang Village, District Sijuk, Belitung Regency. This area is also a central area for producing Sijuk shrimp paste. Census refers to periodic collection of information about the specifi c population from the entire population. Sampling is a method of collecting information from a sample that represents population. The result showed that the Sijuk shrimp paste businesses gives benefi ts because they had a gain of Rp.17.558.914,29 / year, the value of gross profi t ratio of 50.61%, the rate of return per capital investment of 1.02, and the return on the investments amounted to 74.58%. The Sijuk shrimp paste businesses are feasible to continue be had the value of discounted payback period of 1.57 years, the net present value of Rp.18.264.662,44, the internal rate of the return value of 35%, and the profi tability index of 1.78. From the results of the sensitivity analysis concluded that the Sijuk shrimp paste businesses are feasible to continue because the percentage of increase in the maximum operating costs still can be tolerated which is equal to 44,763% and the percentage of maximum reduction in the selling price of Sijuk shrimp paste still can be tolerated which is equal to 22.108%.